Exploring marriage beliefs from the perspectives of married students - Sadeghian, Efat; Ghasemi, Seyed Ali; Maddineshat, Maryam (Frontiers in Psychology, 2025)
IntroductionIranian university students have a positive outlook on marriage; however, certain beliefs may impact their satisfaction with marriage and the quality of their relationships. By examining these beliefs and considering the experiences of married students, valuable information can be gathered to develop policies that protect family rights and support the younger generation.AimThis study aimed to explore the beliefs about marriage from the perspectives of married students.MethodA qualitative study was conducted. University students were selected through purposive sampling at Hamadan University Medical Sciences,…, Iran. Data was collected from October 2022 to January 2023. Semi-structured interviews were held with 24 married students, and the analysis was conducted using conventional content analysis.ResultsIn our research, we thoroughly analyzed 51 beliefs about marriage held by students, categorizing them into eight subcategories, including “empathy and simplifying life,” “keeping affection alive,” “effective and transparent communication,” and others. These beliefs were further condensed into three overarching categories: “intimacy and companionship,” “establishing a secure environment,” and “equity and upholding preexisting convictions.”ConclusionThe research explored the intricate interplay of beliefs shaping university students' beliefs toward marriage. Beliefs surrounding empathy, simplifying life, sustaining affection, and effective and transparent communication contribute to marriage intimacy and compassion. Notably, beliefs concerning security, commitment, and conflict resolution strategies were identified as pivotal for creating a safe marital atmosphere. Furthermore, the presence of beliefs supporting women's autonomy was deemed crucial for fostering equality within marital partnerships, while beliefs endorsing male dominance, religious biases, sexism, and cultural bigotries were found to impact spousal relationships potentially detrimentally.